Hyaluronic Acid Microbial Synthesis and Its Explicit Uses in the Development of Nutraceuticals, Biomedicine, and Vaccine Development - Shukla P.; Srivastava P.; Mishra A. (My University, 2025)
A medicinal biopolymer with high economic value, hyaluronic acid (HA), is increasingly synthesized through microbial fermentation. Research and development have focused on enhancing hyaluronic acid’s crucial quality characteristics, purity, and molecular weight. Due to its adaptability, hyaluronic acid has played a significant role in biomedical research and has been used in numerous sectors, including tissue engineering and cancer treatment, in various forms. Micelles, polymersomes, hydrogels, and other hyaluronic acid-based nanomaterials are essential for effective drug administration and cancer treatment. Modern hyaluronic acid encapsulation techniques can adequately prevent probiotics and nutraceuticals from the severe conditions of food processing. Hyaluronic acid can also create a wide range of vaccinations as an efficient and biocompatible adjuvant. Also, developing nasal vaccinations against infectious diseases is a promising application for hyaluronic acid-coated micelles. This chapter examines the benefits and drawbacks of microbial hyaluronic acid generation and its diverse applicability in various industries. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.